Stigma among healthcare workers towards hepatitis B infection in Bangalore, India: a qualitative study - F. C. van der Scheun; M. C. M. Nagelkerke; A. Kilaru; V. Shridhar; R. Prasad; T. S. van der Werf (BMC, 2019)
Abstract Background With about 50 million people infected with hepatitis B (HBV) in India the burden of disease is high. Stigma has been identified to have a major negative impact on screening, diagnosis and treatment of hepatitis B patients. The aim of this study was to assess the stigma in nurses and physicians in Bangalore, India; studies on stigma in HBV have only been published outside of India. Methods Semi-structured in-depth-interviews were conducted in the period of March 20th and April 16th 2018 to study stigma and other problems in the care of hepatitis B patients. Stigma was pragmatically defined as a mark of disgrace associated with having a hepatitis B infection. Thirty physicians and nurses in different clinics and hospitals across the city of Bangalore were selected by purposeful sampling and snowball effect until theoretical saturation was reached. Results The following themes were identified during the interviews: feelings when treating a patient; pregnancy and marriage; confidentiality; morality; improvement in care and the difference with HIV. The most stigma was discovered in the theme morality. The majority of our participants mentioned lack of awareness as biggest obstacle in health care of hepatitis B patients. Conclusions This is the first qualitative study in India exploring hepatitis B stigma among health care workers. Stigma was found in certain themes, such as morality. Though, no unwillingness to treat was found. There was a general lack of awareness amongst patients according to our participants and could jeopardize proper treatment. These results will further help in developing strategies to tackle hepatitis B in India.